Correlations, connections, and physics in complex systems - Berche, B.; Folk, R.; Kenna, R.; Mryglod, O. (Condensed Matter Physics, 2017)
It is with great pleasure that we present, in this issue, a series of papers dedicated to the 60th birthday
of Professor Yurij Holovatch. The broad spectrum of topics treated by the contributions reflect Yurij’s
comprehensive interests and his wide-ranging research. Thus, contributions range from papers on phasetransition
theory to papers dealing with scientometric issues, from condensed matter theory to cosmological
and astronomical problems.